Estudio de prefactibilidad para la instalación de una planta productora de destilado a base de mucílago de cacao - Acosta Rimachi, Giancarlo Nicolas (2021)
The objective of this research is to demonstrate the technical, economic and financial and social viability of the installation of a producer plant of distillate based on cocoa mucilage, an unused by-product, from the fermentation process of cocoa beans, for its commercialization in Metropolitan Lima through supermarkets, liquor stores, restaurants and minimarkets.